Stem cells-endothelial differentiation in 3D in vitro model - Md Hashim, Siti Nurnasihah; Yusof, Muhammad Fuad Hilmi; Zahari, Wafa’; Chandra, Hamshawagini; Ahmad Amin Noordin, Khairul Bariah; Kannan, Thirumulu Ponnuraj; Sheikh Abdul Hamid, Suzina; Mokhtar@Makhtar, Khairani Idah; Ahmad, Azlina (2018)
lntroduction: Multipotent stem cells are characterized by its self renewal ability and potential to differentiate into many types of cell lineages. This study is focusing on angiogenesis, where the differentiation target is to turn the dental stem cells into endothelial-like cells. Thus, a 3D human amniotic membrane (HAM)-based in vitro model mimicking angiogeneic microenvironment is proposed to further understand the endothelial differentiation process. The 3D human amniotic membrane (HAM)-based scaffold is made up of stem cells from human exfoliated deciduous teeth (SHED) cultured on HAM with the addition of vascular endothelial growth factor (VEGF). Objectives: To determine the capability of SHED to undergo endothelial-like differentiation on a 3D HAM-based model. Methodology: SHED was cultured in a complete medium of alpha-minimum essential medium (a-MEM). De-epithelialised glycerol-preserved HAM was used as a scaffold while VEGF was added to induce angiogenesis. Cells were cultured in 3 groups, namely, SHED treated with VEGF (SV), SHED cultured on HAM (SA) and SHED cultured on HAM treated with VEGF (SAV). The endothelial differentiation was evaluated by scanning electron microscope (SEM), haematoxylin and eosin (H&E) and one-step RT-PCR Results: The result of SEM showed that SHED had successfully differentiated into endothelial-like cells. Through H&E staining, SHED was found forming a monolayer structure on the stromal side of HAM from day 1 until 14 but infiltrated into the structure at day 21. Meanwhile, gene expression analysis revealed that treated SHED was able to retain its stemness along with the expression of endothelial markers. Conclusion: Our 3D HAM-based in vitro model with the addition of VEGF was able to promote SHED-endothelial differentiation.